Innovation Systems in the European Periphery: the Case of Ireland and Greece - Patrick Collins; Dimitrios Pontikakis (European Regional Science Association (ERSA), 2006)
Two decades ago, Greece and Ireland stood passive spectators of political, economic and technological developments at the core of an emerging European Economic Community. Away from the industrial centres of Europe, the attainment and application of new ideas, it seemed, had no place among the prescriptions of policy. The pursuit of each country's comparative advantage dictated that they be net consumers of technological wares invented elsewhere. And while a lot has changed in the meantime, a great deal has also endured. Today, innovation is no longer confined to the fringes of industrial policy; it features prominently, throughout the continent, as 'the solution' to the re-discovered riddle of competitiveness. Ideas on how to best mobilise intellectual assets for innovation abound. Theory suggests that institutions are important in shaping productive efforts towards innovation; the experiences of Ireland and Greece offer a fitting testing ground. Ireland has made strides in the FDI route to prosperity, no longer labelled a cohesion country. Greece however faces pressing economic problems, in the aftermath of celebrated, largesse-fuelled growth. Over the period in question though, nowhere else have the differences between the two countries become more accentuated (and apparent), as in matters of innovation. We propose that the key to these differences lies with the drafting of policy and the consequent shaping of their institutions. We observe that importing solutions from abroad, with Greece looking to Brussels and Ireland to the US, was central to their respective experiences.
Keywords: 330